LPS Mediates Bovine Endometrial Epithelial Cell Pyroptosis Directly Through Both NLRP3 Classical and Non-Classical Inflammasome Pathways - Ma, Xiaoyu; Li, Yajuan; Shen, Wenxiang; Oladejo, Ayodele Olaolu; Yang, Jie; Jiang, Wei; Imam, Bereket Habte; Wu, Xiaohu; Ding, Xuezhi; Yang, Ying; Wang, Shengyi; Yan, Zuoting (Frontiers in Immunology, 2021)
To study the molecular pathological mechanism of bovine endometritis, this study took bovine endometrial epithelial cells (BEEC) as the research object and built the cell inflammation model by using different concentrations (0, 3, 10, 30ug / mL) of lipopolysaccharide (LPS) for 24h. Cell secretion was collected, centrifuged, then detected the lactate dehydrogenase (LDH) activity and the content of related inflammatory factors (IL-6, IL-1β, and TNF-α) in the extracellular fluid. The cells were also collected, then total RNA and total protein were extracted. The related mRNAs (IL-6, IL-10, TNF-α, IL-1β, IL-18, NLRP3, ASC, CASPASE-1, CASPASE-4, and GSDMD) and proteins (NLRP3, ASC, CASPASE-1, CASPASE-4, and GSDMD) were detected by Real-time PCR(RT-PCR) and Western Blot(WB). The results showed that: ① After 24 hours of treatment with LPS concentrations of 3, 10, and 30 ug / mL, a cellular inflammation model of BEEC was successfully constructed. ② After 24 hours of treatment with LPS concentrations of 3, 10, and 30 ug / mL, cells may activate GSDMD through classic and non-classical inflammasomes, caused cell Pyroptosis.